PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN PUBLIK TERHADAP SUSTAINABILITY REPORTING - Alfi Raihan Putra (2023)
This research is a quantitative study with the aim of testing and proving institutional ownership has an influence on sustainability reporting and testing and proving public ownership has an influence on sustainability reporting. Measurement in the disclosure of sustainability report using GRI G4. This study uses secondary data obtained from sustainability report reports and annual reports of non-financial companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The purposive sampling technique used in the research testing the sample in the study was 47 companies with a total of 141 samples. Data testing using the STATA version 17 application. Panel data regression was used for data analysis in the study. The results of this study indicate (1) institutional ownership has no significant effect on sustainability reporting, (2) public ownership of institutional ownership has no significant effect on sustainability reporting. In addition, this study found that the control variable company age has an effect on sustainability reporting. Meanwhile, profitability, leverage, and company size have no significant effect on sustainability reporting.